The Henry VIII powers in the Brexit process: justification subject to political and legal safeguards - Kouroutakis, Antonios (Taylor & Francis, 2020)
Henry VIII powers, which are commonly found in legislation, until recently, were not an issue of major constitutional concern. However, their extensive use in the EUWA and the subsequent EUWAA attracted the attention of academics and politicians alike. This article aims to offer justifications for the use of Henry VIII powers in extraordinary situations such as Brexit, given that such powers would be subject to enhanced legal safeguards. In doing so, this article examines the challenge that the Brexit process poses to the law making institutions, and it elaborates on how the proper use of Henry VIII powers has the capacity to meet the Brexit ends. It also focuses on the particular Henry VIII powers in the EUWA and the EUWAA and it examines both the legal and the political safeguards. It evaluates both the legal and the political safeguards and it highlights their positive and negative aspects. Finally, this article concludes with a set of legal safeguards, procedural and material, that are necessary for the proper use of such powers in future legislation. In particular, it argues that the proper use of Henry VIII powers should include at least two safeguards; first a pre-legislative stage attracting public engagement and second a substantive limit according to which the executive should not be allowed to use Henry VIII powers to amend acts of constitutional value and most importantly the enabling act. Accordingly, it proposes that there is need for a constitutional statute to set uniform safeguards and standards for every use of Henry VIII powers.
Keywords: 56 Ciencias Jurídicas y Derecho; ODS 16 - Paz, justicia e instituciones sólidas